Planning, Designing, and Managing Green Roofs and Green Walls for Public Health – An Ecosystem Services Approach - Ode Sang, Åsa; Thorpert, Petra; Fransson, Ann-Mari (Frontiers in Ecology and Evolution, 2022)
Installing green roofs and green walls in urban areas is suggested to supply multiple ecosystem services of benefit to human health and well-being. In a three-step literature review, we examined current knowledge on the link between public health and green roofs and green walls. A systematic search identified 69 scientific articles on green roofs/walls with a public health discourse. These articles were categorized according to type of health path covered (reduction of temperature, air pollution, noise or environmental appraisal) and coverage of issues of relevance for strategies on planning, design/construction, and maintenance of green roofs and green walls. Articles identified through the structured search were complemented with reviews (with no explicit public health rationale) covering reduction of noise, temperature, or air pollution and environmental appraisal. Other relevant studies were identified through snowballing. Several of the articles provided guidelines for optimizing the effect of green roofs/walls in supporting ecosystem services and maximizing well-being benefits to support health pathways identified. These included specifications about planning issues, with recommended spatial allocation (locations where people live, sun-exposed for maximum ambient temperature reduction) and with physical access needed for environmental appraisal. Recommendations regarding design parameters covered substrate depth (deeper generally being better), plant choices (more diverse roofs providing more services), and maintenance issues (moist substrate positively correlated with heat reduction).